2018
DOI: 10.2478/jwld-2018-0068
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis and sub-watersheds prioritization of Nagmati River watershed, Kutch District, Gujarat using GIS based approach

Abstract: Morphometric analysis of any watershed and its prioritization is one of the important aspects of planning for implementation of management programmes. Present study evaluates the quantitative morphometric characteristics of Nagmati River watershed in Kutch District of Gujarat by utilizing Cartosat-1 data (CartoDEM). In all 19 aerial and 6 linear morphometric parameters of the watershed have been evaluated. Drainage map of the study area reveals a dendritic drainage pattern with sixth order stream network compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…Nearly similar results were also reported by Gupta (2003). A similar geometric relationship is found to exist between the stream order and logarithmic stream length for the Tidi watershed under consideration which further indicates the area to be having uniform underlying lithology, and geologically, there has been no probable uplift (Said et al 2018). The correlation coefficient relation of stream order with log stream length for the current study was found 0.97 and shown in Figure 4(b).…”
Section: Relation Of Stream Order With Log Stream Number and Log Stre...supporting
confidence: 75%
“…Nearly similar results were also reported by Gupta (2003). A similar geometric relationship is found to exist between the stream order and logarithmic stream length for the Tidi watershed under consideration which further indicates the area to be having uniform underlying lithology, and geologically, there has been no probable uplift (Said et al 2018). The correlation coefficient relation of stream order with log stream length for the current study was found 0.97 and shown in Figure 4(b).…”
Section: Relation Of Stream Order With Log Stream Number and Log Stre...supporting
confidence: 75%
“…Areal aspects of morphometric parameters have been used worldwide for erosion risk area prioritization ( Aher et al., 2014 ; Altaf et al., 2014 ; Said et al., 2018 ). They have direct relations to erosion events such as drainage density (D d ), drainage texture (D t ) and stream frequency ( Figure 3 ) and indirect ties to erodibilty factor including circularity ratio (R c ), elongation ratio (R e ), form factor (F f ) and channel compactness (C c ).…”
Section: Resultsmentioning
confidence: 99%
“…This parameter is basin lithology dependents and is an indication of the basin drainage network texture (31). The low drainage frequency for the study watersheds indicates that the watersheds are bearing low relief and having conducting subsurface materials (28). It is also evident from Table 1 that the texture ratio ranges from as low as 0.356 for WS2 to as high as 3.642 for WS14 and the rest of the watersheds fell between these two extremes.…”
Section: Linear Aspectsmentioning
confidence: 87%